2021
DOI: 10.4103/ccd.ccd_561_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postoperative Pain after Pulpectomy using Different File Systems in Primary Teeth

Abstract: Objective: The purpose of this systematic review was to compare the incidence and intensity of postoperative pain after pulpectomy using different instrumentations in primary teeth. Materials and Methods: An extensive literature search in PubMed, Cochrane Library, Science Direct, LILAC, SIGLE, and Google Scholar was performed to identify English language articles with human subjects that evaluated the effects of different instruments on postoperative pain after pulpecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Pulpectomies have been associated with postoperative pain. Reporting post-endodontic pain has been found to be subjective, usually due to the extrusion of debris [17]. The placement of multiple stainless crowns in a single appointment can result in pain due to changes in occlusion or an increase in vertical dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Pulpectomies have been associated with postoperative pain. Reporting post-endodontic pain has been found to be subjective, usually due to the extrusion of debris [17]. The placement of multiple stainless crowns in a single appointment can result in pain due to changes in occlusion or an increase in vertical dimension.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing manual, rotary and reciprocal files, they found less postoperative pain in the last two as opposed to manual files [33,34] . Lakshmanan et al concluded that rotary systems allow a lower intensity and incidence of postoperative pain in root canal treatment of primary teeth [35] . Rotary files have shown a reduction in postoperative pain, which is effective in the management of pediatric patients' behavior and has a positive influence on them.…”
Section: Postoperative Painmentioning
confidence: 99%
“…Post-operative pain is considered to develop as a response to the acute inflammation caused by extrusion of dentinal debris, microorganisms, pulpal tissue, and irrigants into the periapical tissues during biomechanical preparation [7]. Only limited studies have evaluated the association of instrumentation technique in causing post-operative pain following pulpectomy in primary teeth [8].…”
Section: Introductionmentioning
confidence: 99%